Izhodišča in posledice komunikacijskega in tradicionalnega načrtovanja pouka književnosti - Saksida, Igor (Jezik in slovstvo, 2019)
Communicative literature teaching in primary school is derived from a concept of reading competence that interlaces motivational factors, reading strategies and knowledge of the basic elements of literature as a system. Literature is an autonomous mode of expression and cannot be subordinated to other fields. Instruction is planned on the basis of literary theory, while also taking into account the reader and the relevance of the text for him/her. The principle of the continuity of school interpretation is consistently applied.
Keywords: bralna zmožnost; izobraževalni programi; izvedba pouka; književnost; komunikacijski pouk; načrtovanje pouka; osnovne šole; pouk književnosti